PENGARUH KOMPETENSI TERHADAP KINERJA PEGAWAI PADA KANTOR CAMAT TELUKDALAM KABUPATEN NIAS SELATAN - Pius Zagoto (Universitas Nias Raya, 2026)
This study aims to determine the effect of Competence on Employee Performance at the Telukdalam District Office, South Nias Regency. This type of research uses quantitative research that is causal in nature. The source of the type of data collected by the researcher is primary data obtained directly from the research location, namely by distributing questionnaires to all employees of the Telukdalam District Office, South Nias Regency. The population in this study were all those who worked at the Telukdalam District Office, South Nias Regency, as many as 30 people. and were used as samples based on the results of the study. The data analysis technique used in this study was simple linear regression analysis. Simple regression analysis is a statistical analysis approach used to describe the relationship between the dependent variable (Employee Performance) and the independent variable. (Competence). Based on the partial test, the Competence variable has a positive and significant effect on employee performance at the Telukdalam District Office, South Nias Regency. The author's suggestion is that in the world of work, expertise or competence is needed to be able to complete tasks or a job quickly and accurately, for that employees should get a form of short-term socialization or education in increasing knowledge in completing tasks or jobs.